Crosstalk of mTOR/PKM2 and STAT3/c‐Myc signaling pathways regulate the energy metabolism and acidic microenvironment of gastric cancer. Issue 2 (11th November 2018) - Gao, Sumeng; Chen, Min; Wei, Wei; Zhang, Xiaoqi; Zhang, Mingming; Yao, Yuling; Lv, Ying; Ling, Tingsheng; Wang, Lei; Zou, Xiaoping
Abstract: Cancer cells consume large amounts of glucose to produce lactate, even in the presence of ample oxygen. This phenomenon is called the Warburg effect. c‐Myc is an important member of the Myc gene family and is involved in the development of various tumors. It plays an important role in the regulation of tumor energy metabolism, which can regulate glycolysis to promote the Warburg effect in a tumor. Our study aimed to improve the malignant biological behavior by controlling the energy metabolism of gastric cancer through the mTOR/PKM2 and signal transduction and activator 3 (STAT3)/c‐Myc signaling pathways through a series of in vitro experiments. Human gastric cancer AGS and HGC‐27 cells were treated with PKM2 and c‐Myc lentivirus, and the effects of the knockdown of PKM2 and/or c‐Myc were analyzed on cell proliferation, cell apoptosis, the ability of cell migration, and the growth signaling pathway in vitro. The expressions of PKM2, c‐Myc, LDHA, STAT3, P‐STAT3, GLUT‐1 gene were identified by the quantitative real‐time polymerase chain reaction and Western blot analysis. Lactate and glucose levels were tested by the corresponding kit. Our findings showed that PKM2 and c‐Myc were upregulated in human gastric cancer. Knockdown of c‐Myc in gastric cancer cells suppressed cell proliferation capacity and glycolysis level, and the inhibitory effects on gastric cancer cells upon co‐knockdown of PKM2 and c‐Myc were more obvious compared with knockout of PKM2 or c‐Myc alone. And there was a correlation between the mTOR/PKM2 and the STAT3/c‐Myc signaling pathways. Our results suggested that c‐Myc might be considered a potential therapeutic target for gastric cancer and PKM2 combined with c‐Myc could better inhibit the malignant biological behaviors of gastric cancer. Abstract : Our results suggested that c‐Myc might be considered a potential therapeutic target for gastric cancer and PKM2 combined with c‐Myc could better inhibit the malignant biological behaviors of gastric cancer.